El litigio de las palabras: Diálogo sobre la política del lenguaje. Jacques Rancière y Javier Bassas. (Ned Ediciones, edición de Kindle, 2019) - Vargas Guevara, Camilo (2023)
We present below a small review of the book Les mots et les torts. Dialogue sur la politique du langage, written by Jacques Rancière and Javier Bassas at the end of 2019, elaborated from a selection of the main themes addressed by the authors in the text.